Todd’s Paresis as a Postictal Phenomenon in Post-Traumatic Epilepsy: A Case Report - I Gusti Agung Ayu Andra Yusari; Ni Made Susilawathi; Ni Putu Ayu Putri Mahadewi (AKSONA, 2025)
Highlight: Todd’s paresis presented as transient hemiparesis in a case of untreated post-traumatic epilepsy. Proposed pathomechanisms of Todd’s paresis include neuronal exhaustion, active inhibition, and postictal hypoperfusion. Todd’s paresis was commonly misdiagnosed as acute ischemic stroke due to the similar clinical presentation   ABSTRACT Introduction: Todd’s paresis is defined as a paralysis state after an epileptic seizure that lasts for several hours to days and recovers completely afterwards. It usually manifests as a transient hemiparesis after a focal or generalized seizure. Todd’s paresis cases and its mechanisms were still widely discussed. Case: A 48-year-old man with history of post-traumatic epilepsy presented with right-sided hemiparesis and facial weakness after a general motor tonic-clonic seizure. The location of the hemiparesis was contralateral to the post-trauma lesion in left frontal lobe which was suspected to be the focus of the seizure. The postictal weakness resolved completely after 30 hours without any specific intervention. It was revealed that the patient had been having several seizures beforehand after the epidural and subdural hematoma due to head trauma. The patient was diagnosed as Todd’s paresis following a post ictal condition in patient with post-traumatic epilepsy. Conclusion: Todd’s paresis should be considered as a diagnosis in patients with seizure and stroke-like syndrome such as hemiparesis due to its similar manifestations, especially if it resolves within hours. Several mechanisms were suggested to be the pathophysiology of Todd’s paresis including neuronal exhaustion, active inhibition, and postictal hypoperfusion.